Death and liver transplantation within 2 years of onset of drug‐induced liver injury. Issue 4 (26th August 2017) - Hayashi, Paul H.; Rockey, Don C.; Fontana, Robert J.; Tillmann, Hans L.; Kaplowitz, Neil; Barnhart, Huiman X.; Gu, Jiezhan; Chalasani, Naga P.; Reddy, K. Rajender; Sherker, Averell H.; Hoofnagle, Jay H.; ,
Abstract : Drug‐induced liver injury (DILI) is an important cause of death and indication for liver transplantation (fatality). The role of DILI in these fatalities is poorly characterized, particularly when fatalities occur >26 weeks after DILI onset. We analyzed patients in the US Drug‐Induced Liver Injury Network prospective study having a fatal outcome within 2 years of onset. Each case was reviewed by eight network investigators and categorized as DILI having a primary, a contributory, or no role in the fatality. We subcategorized primary role cases as acute, chronic, acute‐on‐chronic, or acute cholestatic liver failure. For contributory and no role cases, we assigned a primary cause of death. Among 1, 089 patients, 107 (9.8%) fatalities occurred within 2 years. DILI had a primary role in 68 (64%), a contributory role in 15 (14%), and no role in 22 (21%); 2 had insufficient data. Among primary role cases, 74% had acute, 13% chronic, 7% acute on chronic, and 6% acute cholestatic failure. For the 15 contributory role cases, common causes of death included sepsis, malignancy, and severe cutaneous reactions with multiorgan failure. For the 22 no role cases, malignancies accounted for most fatalities. Higher bilirubin, coagulopathy, leukocytosis, and thrombocytopenia were independently associated with DILI fatalities. New R ratio Hy's law had a higher positive predictive value for overall fatality (14% versus 10%) and a stronger independent association with DILI fatalities within 26 weeks compared to the original version of Hy's law (hazard ratio, 6.2, 95% confidence interval 3.4‐11.1, versus 2.2, 95% confidence interval 1.3‐3.7). Conclusions: DILI leads directly or indirectly to fatality in 7.6% of cases; 40% of these had nonacute liver failure courses. New R ratio Hy's law better identifies risk for death compared to the original Hy's law. (Hepatology 2017;66:1275‐1285).